استراتيجيات تعليم مهارة الاتصال الشفوي باللغة العربية لغير الناطقين بها: تجارب شخصية / The teaching strategies of oral communication skills in Arabic for non-native Arabic speakers: Personal experience - Mohammad, Ismail Hasanein Ahmed (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2016)
ملخص البحث: يعتبر الاتصال الشفوي (الكلام) الوسيلة الفاعلة في بلورة الفكرة الكامنة لدى الفرد، وإخراجها بصورة صوتية تمثل تلك الفكرة تمثيلاً واضحاً، وإيصالها إلى الطرف الآخر –المستمع-دون لبس أو غموض، ويرى الباحث أن الطلبة غير العرب عند التّحدث باللغة العربية يتعثرون على الرغم من تخصصهم في تعلُّمِها بوصفها لغة ثانية. تهدف هذه الدراسة إلى معرفة أسباب إحجام الطلبة عن التحدث باللغة العربية، ومن ثَمَّ إبراز بعض الاستراتيجيات التي استخدمها الباحث في تعليم مهارة الاتصال الشفوي لطلبة بكالوريوس التربية، تخصص تعليم لغة عربية بوصفها لغة ثانية على مدى الخمس السنوات الماضية بالجامعة الإسلامية العالمية بماليزيا. توصلت الدراسة إلى أن تعليم وتعلم اللغة العربية خارج موطنها يعتريه كثير من العقبات تتمثل في البيئة المحيطة بالدارس، والمناهج والمقررات، والوسائل المعينة اللازمة، وينبغي أن يخصص وقت لممارسة الكلام باللغة العربية داخل الصفوف الدراسية، وإتاحة الفرصة لكل طالب أو طالبة في التعبير الشفوي، مع التشجيع الكامل من المعلم، ويتم تصحيح الخطأ بطريقة محفزة، وترصد لهم مكافآت ولو رمزية، تعزيزاً لدفعهم للكلام، وكسر حاجز الخوف والخجل، وإكسابهم الجسارة والجرأة والثقة. على أن يكون الوقت المخصص للكلام إلزاميا لجميع الطلبة دارسي اللغة العربية، ولكل المقررات المتعلقة باللغة. الكلمات المفتاحية: إحجام الطلبة - التخصص – اللغة الثانية- الاتصال الشفوي - الاستراتيجيات. Abstract: The oral communication (speech) is the effective method in developing the idea of the individual and to present it in clear representation and delivery to the other party — the listener-unambiguously. Since the oral communication is one of major concern of the target language, the teaching and learning requires using a variety of strategies to achieve the goal of language learning. The focus of this paper is the oral communication difficulties faced by non-Arab speaking students despite their specialization in learning Arabic as a second language. Therefore this paper aims to find out reasons why students con not communicate well in Arabic Language, and highlight some of the strategies used by the researcher in the teaching of oral communication skills for the Bachelor of education students, specializing in teaching Arabic as a second Language over the past five years in the International Islamic University-Malaysia, where the strategies used had great impact in breaking the barrier of shyness of speaking in Arabic, and improved their performance in oral expression in multiple areas. From these strategies; the use of multimedia presentation, questions and answers, the excitement by viewing the strange or fantastic scenes that evoke the students to express them orally, and movements, representation, simulation and other strategies that draw the attention of students and encourages them to speak. As well as the cooperation and interaction between teacher and students and among the students themselves. The descriptive methodology will be applied in this paper to explore the teaching strategies implemented by the researcher in teaching oral communication skill, which shown great impact on students achievements. Key Words: Motivating student – Major – Second language – Oral communication – strategies. Abstrak: Pertuturan lisan ialah satu cara berkesan dalam mengembang idea seseorang itu untuk menjelaskan maksud kepada pihak kedua tanpa kesamaran. Memandangkan pertuturan lisan adalah satu aspek fokus bahasa yang dipelajari, pembeljaran dan pengajarannya memerlukan beberapa strategi untuk mencapai tujuan pembelajaran bahasa. Tumpuan kertas ini ialah terhadap permasalahan komunikasi yang dialami oleh pelajar bukan Arab walaupun mereka adalah pelajar pengkhususan Bahasa Arab sebagai bahasa kedua. Perbincangan tertumpuuntuk mencari sebab kelemahan pertuturan komunikasi lisan para pelajar dalam bahasa Arab dan beberapa strategi yang digunakan oleh penulis dalam mengajar kemahiran pertuturan lisan bahasa Arab untuk pelajar Sarjana Muda Bahasa Arab Pendidikan daripada lebih lima tahun pengalaman beliau di Universiti Islam Antarabangsa Malaysia. Startegi tersebut dilihat dapat memberi kesan dalam memecah kebuntuan sikap malu para pelajar bertutur dalam bahasa Arab dan meningkatkan penguasaan mereka dalam pelbagai bidang. Di antara strategi ini ialah: penggunaan multi-media, soal jawab, rasa kagum apabila diperlihatkan gambar yang pelik dan menarik menjadikanpelajar ingin menyatakan pendapat mereka secara lisan. Strategi lain juga termasuk: pergerakan, penampilan, simulasi dan pelbagai strategi yang menggalakkan pelajar bertutur serta sikap saling membantu dan interaksi di antara pensyarah dan pelajar. Kertas ini menggunakan metod deskriptif. Kata kunci: Menggalakkan pelajar – pengkhususan – bahasa kedua – petuturan lisan – strategi.